Motivasi Melanjutkan Pendidikan Perguruan Tinggi Siswa SMA Muhammadiyah 8 Cerme - Lazuardi Muhammad (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
The education system in Indonesia is expected for a student to have good character, have extensive knowledge, to have the provisions to be able to compete in today's modern era. Education is seen as one aspect that has an important role in shaping the quality of future generations. Higher education has benefits that are no less important for individual life, including providing changes in a good and quality standard of living such as more decent jobs and income, having a wider and beneficial level of association for the future, having knowledge and high creativity that is used for life. everyday life and compete in the world of work, also more valued in living a lifestyle. Expectations related to a better quality of life after attending tertiary education will not work as expected if there is no encouragement or motivation to continue on to tertiary education. Many factors become obstacles in continuing tertiary education including family economic factors, the cost of education and the difficulty of pursuing tertiary education. The purpose of this research is to measure students' motivation in continuing their higher education. The method used is quantitative experiment, with a total population of 133 people. The sampling technique used is random sampling by selecting 50 subjects. Data collection techniques in this study used observation and interview techniques. Data analysis was performed using a non-parametric paired sample t test. The results of the research show that the asymp sig value is 0.017 <0.05, from these results it can be concluded that there is an increase in student motivation in continuing higher education.